MultiFaithNet: Religion, Live and Interactive - Fry, Eileen (Proceedings of the International Conference on Networked Learning, 1998)
The original proposals for MultiFaithNet were, developed by the Webmaster, Klaus Stoll, and Dr Paul Weller, Director of the University of Derby’s Religious Resource and Research Centre. MultiFaithNet is sponsored by Derby University Enterprises Ltd and is being developed within the Religious Resource and Research Centre of the School of Education and Social Science. MultiFaithNet works with a panel of consultants drawn from the religious traditions which it covers and from academics with expertise in respect of these traditions. This paper will present an outline of the development of MultiFaithNet: from its inception to global launch on 11 March 1998, describing the various services and their inter relationship with the website that is MultiFaithNet. MultiFaithNet evolved out of and builds upon the track record of the Religious Resource and Research Centre which has already produced in conjunction with The Inter Faith Network for the UK, Religions in the UK: A Multi-Faith Directory (1997) which is widely recognised as a unique and comprehensive guide to faith communities, their organisations and places of worship in the UK.